Study on the damping ratios of reinforced concrete structures from seismic response records. (15th November 2020) - Dai, Kaoshan; Lu, Dan; Zhang, Songhan; Shi, Yuanfeng; Meng, Jiayao; Huang, Zhenhua
Highlights: Developing the storey-by-storey methodology for estimating the damping ratios of RC structures from seismic response data. Studying the correlation between the amplitude of motion and the damping behavior of structure during an earthquake. Proposing an empirical equation for giving an appropriate value of damping ratio in the seismic analysis of RC buildings. Abstract : Abstract: Structural damping ratio, which quantifies the energy dissipation of civil engineering structures under dynamic excitations, plays a critical role in structural seismic design and assessment. However, structural damping ratio is usually identified as an empirical value in design or as an optional parameter for different structure types as suggested in existing building seismic design guidelines. In the present work, the structural damping features of a variety of reinforced concrete (RC) structures under real ground motion excitations are further investigated by processing their response records reported in the Center for Engineering Strong Motion Data (CESMD) database. From the storey-by-storey methodology developed in this study, the equivalent damping ratios of the structures are estimated, and the time-varying effect of damping ratio is further explored, confirming the correlation between the damping ratio and the amplitude of ground motion. Based on a statistical analysis, an empirical relationship between the equivalent damping ratio and the peak ground acceleration (PGA) has been developed and validated, providing civil engineers with a refined basis for reasonably selecting the equivalent damping ratios during either the design or the post-earthquake assessment of RC structures.